Internal doping and external coating type positive electrode material, preparation method thereof, positive plate and lithium ion battery

By doping high-energy phosphate bond material in lithium manganese iron phosphate and covering the carbon layer on the surface, forming an internal doped outer-covered positive electrode material, the problems of low conductivity and low gram capacity of lithium manganese iron phosphate are solved, and higher conductivity and gram capacity and better cycling performance are achieved.

CN119650592APending Publication Date: 2025-03-18JIANGSU PYLON BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411808392.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Lithium manganese ferrophosphate material has low conductivity, Mn dissolution and gas production, resulting in a low gram capacity exertion rate.

Method used

By doping a material containing a high-energy phosphate bond in lithium manganese iron phosphate and covering a carbon layer on the surface, an inner doped outer covering type positive electrode material is formed.

Benefits of technology

It significantly improves the conductivity and gram capacity of the material, improves the cycling performance, and has higher gram capacity and better cycling performance than conventional positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179895530000101
    Figure BDA0005179895530000101
Patent Text Reader

Abstract

The invention provides an internally-doped and externally-coated positive electrode material, a preparation method thereof, a positive plate and a lithium ion battery, and relates to the technical field of batteries. According to the internally-doped and externally-coated positive electrode material provided by the invention, the synergistic effect of the materials containing high-energy phosphate bonds is fully exerted by doping the materials containing the high-energy phosphate bonds in the lithium manganese iron phosphate and coating the surface with the carbon layer, so that the conductivity can be remarkably improved, the gram capacity of the lithium manganese iron phosphate is excited, and compared with a conventional positive electrode material, the material has the advantages that the cost is reduced; and the material has higher gram volume and better cycle performance. The preparation method is simple, and the prepared positive electrode material is good in electrochemical performance and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an internally doped and externally coated positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] Lithium manganese iron phosphate material has an olivine structure similar to that of lithium iron phosphate material, and its theoretical specific capacity is also 170mAh / g. In addition, the electrochemical reaction potential of lithium manganese iron phosphate material is about 4.1V, so its theoretical gram energy is nearly 20% higher than that of lithium iron phosphate, and it has great prospects. However, the conductivity of lithium manganese iron phosphate is much lower than that of lithium iron phosphate, and there are phenomena such as Mn dissolution and gas production, so its gram capacity utilization rate is low, lower than that of lithium iron phosphate. Therefore, improving the gram capacity utilization of lithium manganese iron phosphate is of great significance to the improvement of the utilization value of lithium manganese iron phosphate.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The first object of the present invention is to provide an internally doped and externally coated positive electrode material to solve the above technical problems.

[0005] The second object of the present invention is to provide a method for preparing the above-mentioned internally doped and externally coated positive electrode material.

[0006] The third object of the present invention is to provide a positive electrode sheet.

[0007] A fourth object of the present invention is to provide a lithium ion battery.

[0008] In order to achieve the above objectives, the following technical solutions are adopted:

[0009] In a first aspect, the present invention provides an internally doped and externally coated positive electrode material, including lithium manganese iron phosphate;

[0010] The lithium manganese iron phosphate is doped with a material containing high-energy phosphate bonds;

[0011] The surface of the lithium manganese iron phosphate is coated with a carbon layer.

[0012] As a further technical solution, the chemical formula of the lithium manganese iron phosphate is (Li2O) n LiFe x Mn y PO4;

[0013] Where x+y=1, 0≤x≤1, 0.5≤n≤1.

[0014] As a further technical solution, the material containing high-energy phosphate bonds includes at least one of inositol hexaphosphate, creatine phosphate, phosphoenolpyruvate or adenosine triphosphate.

[0015] As a further technical solution, the molar ratio of carbon atoms in the carbon layer to lithium manganese iron phosphate is 7.2-9.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned internally doped and externally coated positive electrode material, comprising the following steps:

[0017] a. Mixing a material containing a high-energy phosphate bond, a lithium source, an iron source, a manganese source and phosphoric acid in a solvent, and heating the mixture to obtain a precursor of a positive electrode material;

[0018] b. The precursor obtained in step a is mixed with a carbon source, and sintered under an inert atmosphere to prepare an internally doped and externally coated positive electrode material.

[0019] As a further technical solution, the lithium source includes at least one of LiOH or Li2CO3;

[0020] The iron source includes at least one of FeSO4, FeCl2 or Fe(NO3)2;

[0021] The manganese source includes at least one of MnSO4, MnCl2 or Mn(NO3)2;

[0022] The carbon source includes at least one of glucose, sucrose or citric acid;

[0023] The solvent includes at least one of ethylene glycol, N-methylpyrrolidone, xylene or pyromellitic anhydride;

[0024] In step a, the mass fraction of the material containing high-energy phosphate bonds dissolved in the organic solvent is 2% to 6%.

[0025] As a further technical solution, in step a, the reaction temperature is 150-200°C and the reaction time is 6-10 hours.

[0026] As a further technical solution, the sintering temperature is 600-800° C., and the sintering time is 6-8 hours.

[0027] In a third aspect, the present invention provides a positive electrode sheet, wherein the slurry layer of the positive electrode sheet includes the internally doped and externally coated positive electrode material.

[0028] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery is the positive electrode sheet described above.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The internally doped and externally coated positive electrode material provided by the present invention can significantly improve its conductivity and stimulate the gram capacity of lithium manganese iron phosphate by doping a material containing high-energy phosphate bonds in lithium manganese iron phosphate and coating the surface with a carbon layer, thereby giving full play to the synergistic effect of the two, and having a higher gram capacity and better cycle performance than conventional positive electrode materials.

[0031] The preparation method of the invention is simple, the prepared positive electrode material has good electrochemical performance and is suitable for large-scale production. DETAILED DESCRIPTION

[0032] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0033] In a first aspect, the present invention provides an internally doped and externally coated positive electrode material, including lithium manganese iron phosphate;

[0034] The lithium manganese iron phosphate is doped with a material containing high-energy phosphate bonds;

[0035] The surface of the lithium manganese iron phosphate is coated with a carbon layer.

[0036] The present invention promotes the rapid transfer of lithium ions by internally doping a material with high-energy phosphate bonds in a lithium iron manganese phosphate precursor, which can release a large amount of energy when decomposed, significantly improving its conductivity, thereby greatly increasing the gram capacity of the material. Compared with conventional positive electrode materials, the externally doped and internally coated positive electrode material of the present invention has a higher gram capacity and better cycle performance.

[0037] In some optional embodiments, the chemical formula of the lithium manganese iron phosphate is (Li2O) n LiFe x Mn y PO4;

[0038] Where x+y=1, 0≤x≤1, 0.5≤n≤1.

[0039] In some optional embodiments, the material containing high-energy phosphate bonds includes but is not limited to inositol hexaphosphate, creatine phosphate, phosphoenolpyruvate or adenosine triphosphate, or other materials containing high-energy phosphate bonds known to those skilled in the art.

[0040] In some optional embodiments, the molar ratio of carbon atoms in the carbon layer to lithium manganese iron phosphate may be, for example, but not limited to, 7.2, 8 or 9.

[0041] In a second aspect, the present invention provides a method for preparing the above-mentioned internally doped and externally coated positive electrode material, comprising the following steps:

[0042] a. Mixing a material containing a high-energy phosphate bond, a lithium source, an iron source, a manganese source and phosphoric acid in a solvent, and heating the mixture to obtain a precursor of a positive electrode material;

[0043] b. The precursor obtained in step a is mixed with a carbon source, and sintered under an inert atmosphere to prepare an internally doped and externally coated positive electrode material.

[0044] The preparation method of the invention is simple, the prepared positive electrode material has good electrochemical performance and is suitable for large-scale production.

[0045] In some optional embodiments, during the reaction in step a, the mass concentration of the material containing high-energy phosphate bonds is 2% to 6%, for example, 2%, 3%, 4%, 5% or 6%.

[0046] In some optional embodiments, the lithium source includes but is not limited to at least one of LiOH or Li2CO3;

[0047] The iron source includes but is not limited to at least one of FeSO4, FeCl2 or Fe(NO3)2;

[0048] The manganese source includes but is not limited to at least one of MnSO4, MnCl2 or Mn(NO3)2;

[0049] The carbon source is not limited to at least one of glucose, sucrose or citric acid;

[0050] The solvent is, but is not limited to, at least one of ethylene glycol, N-methylpyrrolidone, xylene or pyromellitic anhydride;

[0051] In step a, the mass fraction of the material containing high-energy phosphate bonds dissolved in the organic solvent may be, for example, but not limited to, 2%, 4% or 6%.

[0052] In some optional embodiments, in step a, the reaction temperature may be, but not limited to, 150° C., 180° C. or 200° C., and the reaction time may be, but not limited to, 6 h, 8 h or 10 h.

[0053] In some optional embodiments, the sintering temperature may be, for example, but not limited to, 600° C., 700° C., or 800° C., and the sintering time may be, for example, but not limited to, 6 h, 7 h, or 8 h.

[0054] In some optional embodiments, the gas of the inert atmosphere includes at least one of nitrogen, argon or helium.

[0055] In a third aspect, the present invention provides a positive electrode sheet, wherein the slurry layer of the positive electrode sheet includes the internally doped and externally coated positive electrode material.

[0056] In some optional embodiments, the slurry layer further includes a conductive agent and a binder.

[0057] In the present invention, there is no specific limitation on the conductive agent and the binder. For example, the conductive agent may be Super P, and the binder may be PVDF.

[0058] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery is the positive electrode sheet described above.

[0059] The lithium-ion battery has high capacity and good cycle performance.

[0060] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0061] Example 1

[0062] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0063] Take 4g of inositol hexaphosphate and dissolve it in 96g of ethylene glycol, then add 0.6mol MnSO4, 0.4mol FeSO4, 1.5mol LiOH, and 1mol phosphoric acid, stir continuously, fully dissolve, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted. Heat it in an oil bath at 180°C for 8h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for several times, filter it, and dry it to obtain the precursor of the required positive electrode material; fully physically mix and grind 1.2mol glucose with 1mol of the precursor (calculated according to 1mol of the product lithium manganese iron phosphate, the same applies to the comparative examples below) and place it in a tubular furnace, set the sintering temperature to 800°C, the time to 8h, and the sintering atmosphere to helium. Carbon-coated (Li2O) is obtained 0.25 LiMn 0.6 Fe 0.4 PO4 positive electrode material.

[0064] Example 2

[0065] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0066] Take 3g of creatine phosphate and dissolve it in 97g of xylene, then add 0.5mol MnCl2, 0.5mol FeCl2, 0.5mol Li2CO3, and 1mol phosphoric acid, stir continuously, fully dissolve and react, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted, and heat it in an oil bath at 160°C for 7h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for several times, filter it, and dry it to obtain the precursor of the required positive electrode material; 1.5mol sucrose and 1mol precursor are fully physically mixed and ground, and then placed in a tubular furnace, and the sintering temperature is set to 600°C for 7h, and the sintering atmosphere is argon. Carbon-coated LiMn 0.5 Fe 0.5 PO4 positive electrode material.

[0067] Example 3

[0068] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0069] Take 2g of creatine phosphate and dissolve it in 98g of ethylene glycol, then add 0.8mol Mn(NO3)2, 0.2mol Fe(NO3)2, 1.2mol LiOH, and 1mol phosphoric acid, stir continuously, fully dissolve, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted. Heat it in an oil bath at 150°C for 6h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for several times, filter it, and dry it to obtain the precursor of the required positive electrode material; mix 1.6mol citric acid and 1mol of the precursor physically, grind them, and place them in a tubular furnace. Set the sintering temperature to 700°C for 7.5h and the sintering atmosphere to nitrogen. Get carbon-coated (Li2O) 0.1 LiMn 0.8 Fe 0.2 PO4 positive electrode material.

[0070] Example 4

[0071] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0072] Take 6g ATP and dissolve it in 94g pyromellitic anhydride, then add 0.7mol MnSO4, 0.3mol FeSO4, 1.3mol LiOH, and 1mol phosphoric acid, stir continuously, fully dissolve, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted. Heat it in an oil bath at 200℃ for 9h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for many times, filter it, and dry it to obtain the precursor of the required positive electrode material; mix 1.7mol glucose with 1mol precursor, grind it and place it in a tubular furnace, set the sintering temperature to 780℃, the time to 6h, and the sintering atmosphere to argon. Carbon-coated (Li2O) is obtained 0.15 LiMn 0.7 Fe 0.3 PO4 positive electrode material.

[0073] Example 5

[0074] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0075] Take 5g of phosphoenolpyruvic acid and dissolve it in 95g of N-methylpyrrolidone, then add 0.2mol MnSO4, 0.8mol FeSO4, 1.8mol LiOH, and 1mol phosphoric acid, stir continuously, fully dissolve, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted. Heat it in an oil bath at 190°C for 9h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for several times, filter it, and dry it to obtain the precursor of the required positive electrode material; mix 1.8mol glucose and 1mol of the precursor physically, grind them, and place them in a tubular furnace. Set the sintering temperature to 650°C for 7h and the sintering atmosphere to nitrogen. Carbon-coated (Li2O) is obtained. 0.4 LiMn 0.2 Fe 0.8 PO4 positive electrode material.

[0076] Example 6

[0077] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0078] Take 3.5g of inositol hexaphosphate and dissolve it in 96.5g of xylene, then add 0.3mol MnSO4, 0.7mol FeCl2, 0.8mol Li2CO3, and 1mol phosphoric acid, stir continuously, fully dissolve, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted. Heat it in an oil bath at 180°C for 10h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for several times, filter it, and dry it to obtain the precursor of the required positive electrode material; mix 1.4mol sucrose with 1mol of the precursor and grind them thoroughly, then place them in a tube furnace, set the sintering temperature to 790°C, the time to 6.8h, and the sintering atmosphere to helium. Carbon-coated (Li2O) is obtained 0.3 LiMn 0.3 Fe 0.7 PO4 positive electrode material.

[0079] Example 7

[0080] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0081] Take 4g of creatine phosphate and dissolve it in 96g of ethylene glycol, then add 0.9mol Mn(NO3)2, 0.1mol Fe(NO3)2, 2mol LiOH, and 1mol phosphoric acid, stir continuously, fully dissolve, and transfer it to a metal reactor containing polytetrafluoroethylene after it is fully reacted. Heat it in an oil bath at 170°C for 8h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for several times, filter it, and dry it to obtain the precursor of the required positive electrode material; mix 1.2mol citric acid and 1mol of the precursor physically, grind them, and place them in a tubular furnace. Set the sintering temperature to 800°C for 6.5h and the sintering atmosphere to nitrogen. Carbon-coated (Li2O) is obtained. 0.5 LiMn 0.9 Fe 0.1 PO4 positive electrode material.

[0082] Example 8

[0083] This embodiment provides an internally doped and externally coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0084] Take 6g of inositol hexaphosphate and dissolve it in 94g of ATP, then add 0.1mol MnSO4, 0.9mol FeSO4, 1mol LiOH, and 1mol phosphoric acid, stir continuously, and fully dissolve. After it is fully reacted, transfer it to a metal reactor containing polytetrafluoroethylene and heat it in an oil bath. The oil bath temperature is 170℃ and the oil bath time is 8h. After the reaction is completed, take out the reactant, wash it with anhydrous ethanol for many times, filter it, and dry it to obtain the precursor of the required positive electrode material; 1.8mol glucose and 1mol precursor are fully physically mixed and ground, and then placed in a tubular furnace, and the sintering temperature is set to 750℃, the time is 8h, and the sintering atmosphere is nitrogen. Carbon-coated LiMn 0.1 Fe 0.9 PO4 positive electrode material.

[0085] Comparative Example 1

[0086] This comparative example provides an undoped, uncoated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0087] Take 0.6mol MnSO4, 0.4mol FeSO4, 1.7mol LiOH, and 1mol phosphoric acid, dissolve them in ethylene glycol, stir continuously, and transfer them to a metal reactor containing polytetrafluoroethylene after sufficient reaction, and heat them in an oil bath at 180℃ for 8h. After the reaction is completed, take out the reactants, wash them with anhydrous ethanol for several times, filter them, and dry them to obtain the precursor of the required positive electrode material; grind the precursor thoroughly and place it in a tube furnace, set the sintering temperature to 800℃, the time to 8h, and the sintering atmosphere to helium. (Li2O) 0.35 LiMn 0.6 Fe 0.4 PO4 positive electrode material.

[0088] Comparative Example 2

[0089] This comparative example provides an undoped, coated lithium manganese iron phosphate positive electrode material, and the preparation method is as follows:

[0090] Take 0.6mol MnSO4, 0.4mol FeSO4, 1.1mol LiOH, and 1mol phosphoric acid, dissolve them in ethylene glycol, stir constantly, and fully dissolve them. After they are fully reacted, transfer them to a metal reactor containing polytetrafluoroethylene, heat them in an oil bath, the oil bath temperature is 180℃, and the oil bath time is 8h. After the reaction is completed, take out the reactants, wash them with anhydrous ethanol for many times, filter them, and dry them to obtain the precursor of the required positive electrode material; 1.2mol glucose and 1mol precursor are fully physically mixed and ground, and then placed in a tubular furnace, and the sintering temperature is set to 800℃, the time is 8h, and the sintering atmosphere is helium. Carbon-coated (Li2O) is obtained 0.05 LiMn 0.6Fe 0.4 PO4 positive electrode material.

[0091] Battery preparation and performance testing:

[0092] (I) Battery preparation:

[0093] Take appropriate amounts of the positive electrode materials of Examples 1 to 8 and Comparative Examples 1-2, respectively, and slurry them with conductive carbon black and polyvinylidene fluoride glue (solid content 6.05%) according to the positive electrode material: conductive carbon black: polyvinylidene fluoride glue (mass ratio) = 92:4:4, and apply them on aluminum foil to prepare positive electrode sheets.

[0094] The positive electrode sheet, separator and lithium sheet are assembled into a battery cell. After liquid injection, a BR2032 shell is used for buckle assembly to obtain a battery.

[0095] (II) Performance test:

[0096] Electrochemical tests were conducted on the battery performance test system with a test voltage range of 2.7V to 4.2V. The battery was tested for charge and discharge cycles at a discharge efficiency of 0.5C. After two weeks of cycling, the charge and discharge test was conducted at 0.5C for 500 cycles. The average value was taken for each group. The test results of the average first discharge capacity and room temperature cycle retention rate (i.e., 500-cycle retention rate) of the battery are shown in Table 1.

[0097] Table 1

[0098]

[0099] It can be seen from Table 1 that the double-layer core-shell positive electrode materials prepared and synthesized in Examples 1 to 8 have better electrochemical properties than those in Comparative Examples 1 and 2. Among them, the material prepared in Example 1 under the preparation and synthesis conditions has better electrochemical properties than the materials prepared under other conditions.

[0100] By comparing Example 1 with Examples 2-8, it can be seen that the internally doped and externally coated positive electrode material can exhibit more excellent performance under appropriate processing conditions and appropriate material ratios.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An internally doped and externally coated positive electrode material, characterized in that: Including lithium manganese iron phosphate; The lithium manganese iron phosphate is doped with a material containing high-energy phosphate bonds; The surface of the lithium manganese iron phosphate is coated with a carbon layer.

2. The internally doped and externally coated positive electrode material according to claim 1, characterized in that: The chemical formula of the lithium manganese iron phosphate is (Li2O) n LiFe x Mn y PO4; Where x+y=1, 0≤x≤1, 0.5≤n≤1.

3. The internally doped and externally coated positive electrode material according to claim 1, characterized in that: The material containing high-energy phosphate bonds includes at least one of inositol hexaphosphate, creatine phosphate, phosphoenolpyruvate or adenosine triphosphate.

4. The internally doped and externally coated positive electrode material according to claim 1, characterized in that: The molar ratio of carbon atoms in the carbon layer to lithium manganese iron phosphate is 7.2-9.

5. The method for preparing the internally doped and externally coated positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: a. Mixing a material containing a high-energy phosphate bond, a lithium source, an iron source, a manganese source and phosphoric acid in a solvent, and heating the mixture to obtain a precursor of a positive electrode material; b. The precursor obtained in step a is mixed with a carbon source, and sintered under an inert atmosphere to prepare an internally doped and externally coated positive electrode material.

6. The preparation method according to claim 5, characterized in that: The lithium source includes at least one of LiOH or Li2CO3; The iron source includes at least one of FeSO4, FeCl2 or Fe(NO3)2; The manganese source includes at least one of MnSO4, MnCl2 or Mn(NO3)2; The carbon source includes at least one of glucose, sucrose or citric acid; The solvent includes at least one of ethylene glycol, N-methylpyrrolidone, xylene or pyromellitic anhydride; In step a, the mass fraction of the material containing high-energy phosphate bonds dissolved in the organic solvent is 2% to 6%.

7. The preparation method according to claim 5, characterized in that: In step a, the reaction temperature is 150-200° C. and the reaction time is 6-10 hours.

8. The preparation method according to claim 5, characterized in that: The sintering temperature is 600-800° C., and the sintering time is 6-8 hours.

9. A positive electrode sheet, characterized in that: The slurry layer of the positive electrode sheet includes the internally doped and externally coated positive electrode material according to any one of claims 1 to 4.

10. A lithium ion battery, characterized in that: The positive electrode sheet of the lithium-ion battery is the positive electrode sheet according to claim 9.